Chronic Vasomotor Allergic Rhinitis (Texas Journal of Medical Science, 2023)
In recent years, there has been a significant increase in the prevalence of diseases of the nose and paranasal sinuses (NPS). Inflammatory diseases of the nasal mucosa (rhinitis) are accompanied by difficulty in nasal breathing and nasal discharge. Chronic forms of rhinitis affect 10–20% of the population, and in epidemiological studies, 40% of respondents report symptoms of rhinitis. In this article, specific aspects of chronic vasomotor allergic rhinitis and treatment methods are considered